Evaluation of the Upper Paraná River discharge controlled by reservoirs - EE. Souza Filho (Brazilian Journal of Biology)
The building of large dams in the Upper Paraná River basin altered the discharge regime at the Porto São José River section. The discharge regime has been altered since 1972, but the changes intensified after the Porto Primavera damming, in late 1998. Considering that discharge control affects the relationship between channel and floodplain, this work aimed to evaluate the intensity of the discharge control that resulted from the operation of the Porto Primavera Dam. To achieve this objective, statistical analyses were carried out based on the Porto São José Fluviometric Station historical series of river level readings and discharge, between 1964 and 2007. Results showed that the average discharge increased from 1964 to 1981 and diminished after river damming. The increase of average discharge rates was followed by an increase of the duration of higher discharges at different levels of geomorphologic and limnological importance, and the reduction of average discharge during the last observed period was followed by a disproportionate decrease in the duration of the abovementioned discharges. Moreover, it is clear that the relationship between fluviometric level and fluvial discharge changed, which implies that a certain river level reading represents a higher discharge than necessary before river damming.